- Thread starter
- #1

- Apr 14, 2013

- 4,601

Let $1\leq n\in \mathbb{N}$. For $0_{\mathbb{R}^n}\neq x\in \mathbb{R}^n$ we define the map $$\sigma_x:\mathbb{R}^n\rightarrow \mathbb{R}^n, \ v\mapsto v-2\frac{x\cdot v}{x\cdot x}x$$

Show that:

- The map is linear.
- It holds that $\sigma_x\in \text{Sym}(\mathbb{R}^n)$ and $\sigma_x=\sigma_x^{-1}$.
- For all $v,w\in \mathbb{R}$ it holds that $v\cdot w=\sigma_x(v)\cdot \sigma_x(w)$.
- Let $n=2$. Determine a vector $v\in \mathbb{R}^2$ such that $\sigma_v=\sigma_a$, where $\sigma_a$ is

the reflection on the straight line through the origin, where $a$ describes the angle between the straight line and the positive $x$-axis.

I have done the following:

- $\sigma_x$ is additive:

\begin{align*}\sigma_x(v+w)&=(v+w)-2\frac{x\cdot (v+w)}{x\cdot x}x=(v+w)-2\frac{\sum_{i=1}^nx_i\cdot (v+w)_i}{x\cdot x}x\\ & =(v+w)-2\frac{\sum_{i=1}^nx_i\cdot v_i+\sum_{i=1}^nx_i\cdot w_i}{x\cdot x}x=(v+w)-2\left(\frac{\sum_{i=1}^nx_i\cdot v_i}{x\cdot x}+\frac{\sum_{i=1}^nx_i\cdot w_i}{x\cdot x}\right )x \\ & =(v+w)-2\frac{\sum_{i=1}^nx_i\cdot v_i}{x\cdot x}x-2\frac{\sum_{i=1}^nx_i\cdot w_i}{x\cdot x}x=v-2\frac{\sum_{i=1}^nx_i\cdot v_i}{x\cdot x}x+w-2\frac{\sum_{i=1}^nx_i\cdot w_i}{x\cdot x}x \\ & = \sigma_x(v)+\sigma_x(w)\end{align*}

$\sigma_x$ is homogeneous:

\begin{align*}\sigma_x(rv)&=(rv)-2\frac{x\cdot (rv)}{x\cdot x}x=rv-2\frac{\sum_{i=1}^nx_i\cdot (rv)_i}{x\cdot x}x\\ & =rv-r2\frac{\sum_{i=1}^nx_i\cdot v_i}{x\cdot x}x=r\left (v-2\frac{\sum_{i=1}^nx_i\cdot v_i}{x\cdot x}\right ) \\ & = r\sigma_x(v)\end{align*}

Therefore the map $\sigma_x$ is linear.

- Could you give me a hint how we can show that?

- \begin{align*}\sigma_x(v)\cdot \sigma_x(w)&=\left (v-2\frac{x\cdot v}{x\cdot x}x\right )\cdot \left (w-2\frac{x\cdot w}{x\cdot x}x\right )=v\cdot w -2\frac{x\cdot w}{x\cdot x}v\cdot x-2\frac{x\cdot v}{x\cdot x}w\cdot x+4\frac{x\cdot v}{x\cdot x}\frac{x\cdot w}{x\cdot x}x\cdot x \\ & =v\cdot w -2\frac{(x\cdot w)(v\cdot x)}{x\cdot x}-2\frac{(x\cdot v)(w\cdot x)}{x\cdot x}+4\frac{(x\cdot v)(x\cdot w)}{x\cdot x}=v\cdot w -4\frac{(x\cdot w)(v\cdot x)}{x\cdot x}+4\frac{(x\cdot v)(x\cdot w)}{x\cdot x}\\ & =v\cdot w\end{align*}

- How can we find such a vector? Do we use the matrix of the map of $\sigma_a$ ?